2019
DOI: 10.1126/science.aau1682
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the protein kinase Pf CLK3 as a multistage cross-species malarial drug target

Abstract: The requirement for next-generation antimalarials to be both curative and transmission-blocking necessitates the identification of previously undiscovered druggable molecular pathways. We identified a selective inhibitor of the Plasmodium falciparum protein kinase PfCLK3, which we used in combination with chemogenetics to validate PfCLK3 as a drug target acting at multiple parasite life stages. Consistent with a role for PfCLK3 in RNA splicing, inhibition resulted in the down-regulation of more than 400 essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 50 publications
2
99
0
Order By: Relevance
“…Finally, it has been reported that inhibition of CLK3 in Plasmodium falciparum ( Pf CLK3) represents a promising approach for the treatment of malaria via preventing the splicing of essential parasite genes. It has been demonstrated that CLK3 inhibition can kill multiple species of malaria parasites at the blood stage and at the liver-stage and block transmission of the parasite to mosquitoes [ 130 , 131 ]. Another indication where CLK inhibition could be therapeutically relevant is Legionellosis, where CLK inhibition (by TG003) was demonstrated to reduce Legionella growth within mouse macrophages [ 132 ].…”
Section: Clks As Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it has been reported that inhibition of CLK3 in Plasmodium falciparum ( Pf CLK3) represents a promising approach for the treatment of malaria via preventing the splicing of essential parasite genes. It has been demonstrated that CLK3 inhibition can kill multiple species of malaria parasites at the blood stage and at the liver-stage and block transmission of the parasite to mosquitoes [ 130 , 131 ]. Another indication where CLK inhibition could be therapeutically relevant is Legionellosis, where CLK inhibition (by TG003) was demonstrated to reduce Legionella growth within mouse macrophages [ 132 ].…”
Section: Clks As Therapeutic Targetsmentioning
confidence: 99%
“…The compound Lead-30 as well as its precursor, the screening hit TCMDC-135051 ( Figure 30 ), were published very recently [ 130 , 131 ]. Both TCMDC-135051 and Lead-30 inhibit Pf CLK3 in Plasmodium falciparum (IC 50 = 40 nM and 19 nM, respectively).…”
Section: Small-molecule Clk Inhibitorsmentioning
confidence: 99%
“…Antimalarial Set (TCAMS) resulted in the discovery of TCMDC-135051 (1, Figure 1), a compound with nM activity against PfCLK3 in in vitro kinase assays and sub µM parasiticidal activity in blood stage P. falciparum (Figure 1). 13 Subsequent studies revealed that TCMDC- 7-Azaindoles are a widely studied pharmacophore incorporated in several therapeutic agents. 14 Kinases are the predominate target with the 7-azaindole moiety generally interacting at the ATP binding site within the kinase hinge region.…”
Section: Screening Of ~25000 Compounds Including All 13533 Compoundmentioning
confidence: 99%
“…Screening of ~25,000 compounds including all 13,533 compounds of the Tres Cantos Antimalarial Set (TCAMS) resulted in the discovery of TCMDC-135051 (1, Figure 1), a compound with nM activity against PfCLK3 in in vitro kinase assays and sub µM parasiticidal activity in blood stage P. falciparum (Figure 1). 13 Subsequent studies revealed that TCMDC-135051 rapidly killed P. falciparum at the trophozoite to schizont stages as well as preventing the development of stage V gametocytes and inhibition the development of liver stage parasites. Our recent studies have therefore validated PfCLK3 as a target with the potential to deliver a curative treatment, be transmission blocking and act as a prophylactic target.…”
Section: Introductionmentioning
confidence: 99%
“…SAR1 corresponding to analogues 8a-c,13 and 16 were designed to examine the effect of the N-diethyl group of ring-A on antimalarial activity. In analogue 8a, the N-diethyl group was replaced with N-dimethyl group to investigate the effect of alkyl group size and molecular lipophilicity.…”
mentioning
confidence: 99%